2023
DOI: 10.1259/bjr.20220544
|View full text |Cite
|
Sign up to set email alerts
|

Photon-counting detector CT: early clinical experience review

Abstract: Since its development in the 1970’s, X-ray computed tomography (CT) has emerged as a landmark diagnostic imaging modality of modern medicine. Technological advances have been crucial to the success of CT imaging, as they have increasingly enabled improvements in image quality and diagnostic value at increasing radiation dose efficiency. With recent advances in engineering and physics, a novel technology has emerged with the potential to surpass several shortcomings and limitations of current CT systems. Photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 90 publications
(190 reference statements)
0
27
0
1
Order By: Relevance
“…Novel photon-counting detector CT (PCD-CT), which has recently been introduced into clinical practice, has the potential to address these limitations and overcome the weaknesses of previous CT systems. Several review articles have been published explaining the basic principles and clinical advantages of PCD-CT with more or less technical depth, depending on the intended readership 4–13 . In this review, we will focus on recent literature that has grown rapidly since the commercial introduction of a clinically approved PCD-CT and on results from human examinations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Novel photon-counting detector CT (PCD-CT), which has recently been introduced into clinical practice, has the potential to address these limitations and overcome the weaknesses of previous CT systems. Several review articles have been published explaining the basic principles and clinical advantages of PCD-CT with more or less technical depth, depending on the intended readership 4–13 . In this review, we will focus on recent literature that has grown rapidly since the commercial introduction of a clinically approved PCD-CT and on results from human examinations.…”
mentioning
confidence: 99%
“…Several review articles have been published explaining the basic principles and clinical advantages of PCD-CT with more or less technical depth, depending on the intended readership. [4][5][6][7][8][9][10][11][12][13] In this review, we will focus on recent literature that has grown rapidly since the commercial introduction of a clinically approved PCD-CT and on results from human examinations.…”
mentioning
confidence: 99%
“…This results in improved CNR, as energy-resolving PCD-CTs are able to assign higher weight factors to low-energy bins where contrast between tissues is highest. 4,5…”
Section: Beam Hardening and Electronic Noisementioning
confidence: 99%
“…Finally, PCD-CT allows simultaneous multienergy imaging through detection of the continuous energy spectrum of incoming photons. 4,5 The benefit of these new, technically guided opportunities is subject of intensive ongoing research. To date, already several studies have shown advantages of PCD-CT over conventional CT, [6][7][8] including applications for abdominal, vascular, cardiac, or chest imaging and various other fields of radiology may benefit from the new detector technique.…”
mentioning
confidence: 99%
“…Photon Counting -quantenzählende oder spektral -CT ist ein weiterer Meilenstein in der Entwicklung der Computertomographie [41][42][43], die es erlaubt die Strahlenexposition wesentlich zu verringern und die Auflösung zu verbessern. Weiterhin können ähnlich wie bei der Dual Energy CT Spektralbilder zur Differenzierung und Quantifizierung einzelner Materialien erstellt werden.…”
Section: Photon Counting Ctunclassified